Tuntutan Jaksa Terhadap Pencemaran Nama Baik Pasca Putusan MK - Ria Beu; Fence M wantu; Jufryanto Puluhulawa (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to determine the demands of prosecutors at the Bone Bolango district attorney's office regarding defamation on social media and to determine the factors that influence the disparity in prosecutors' demands at the Bone Bolango district attorney's office regarding criminal acts of defamation on social media. The research method used is a type of empirical research, namely a legal research method that functions to see the law in real terms and examine how the law works in society. The results of the research obtained regarding the prosecutor's demands at the Bone Bolango District Prosecutor's Office regarding defamation on social media, there is a disparity in the demands therein, where in the same case the level of material is the same, but the prosecution in both cases is too far apart, this is caused by several factors. These include social reasons, trial facts and statutory regulations. The conclusion that there is a disparity in sentences demanded by public prosecutors was never intended to eliminate the difference in the amount of punishment for criminals, but rather to reduce the range of differences in sentences imposed because this disparity which is too far is contrary to justice and law enforcement and has an impact on the wider community.